(untitled) (Journal of Educational Sciences, 2023)
The relevance of the topic under consideration, due to modern trends in the world of limitless informtion space are indicated in the article. The authors, relying on the requirements outlined in the State obligatory standards of higher and post-graduate education of the Republic of Kazakhstan, consider it necessary to form the public consciousness of students. In this regard, it is necessary to be attentive to information received in a foreign language, in addition, it is important to teach students an analytical and critical attitude to various media information. The method of linguo-stylistic analysis of the text of a publicistic speech is considered as one of the important methods for public consciousness’ formation, the demonstration of the effectiveness of which is the goal of the article’s authors. To achieve this goal, the following tasks are solved: analysis of scientific, pedagogical and methodological literature, determination of an effective algorithm of actions in the linguo-stylistic analysis of the text of a publicistic style of speech, development of indicators and levels of skills to analyze the text. The authors highlight the novelty of the study, which lies in the fact that for the first time the issues of the impact of the linguisticstylistic analysis method of a foreign language text on the formation of the students’ public consciousness. Within the framework of this article, communicative and structural-logical analyzes of the text are described in detail. The authors also consider the issues of linguistic features of publicistic style texts at the level of vocabulary, morphology and syntax. The highest level of correct text perception is the interpretation of the text in the form of an essay-reasoning, essay, oral review. Experimental work was carried out with students of the specialty “Foreign language: two foreign languages”, which gave positive results. The authors applied theoretical and empirical research methods: analysis, systematization and generalization of scientific, scientific-pedagogical, methodical literature, questioning, testing, conversation, experiment. Key words: mass media, public consciousness, publicistic style of speech, text, linguo-stylistic analysis.